1979
DOI: 10.1099/0022-1317-43-3-489
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Morphology of the Bluegill Virus

Abstract: SUMMARYAn enveloped, ether-sensitive, acid-labile virus isolated from Lepomis macrochirus, the bluegill, is described. Virus replication is limited to teleostean cell lines and achieves highest titres in centrarchid cells. As determined by the uptake of tritiated nucleotides and the effect of 6-azauridine and actinomycin D on replication, the virus genome is RNA. The virus has no haemagglutinin or neuraminidase nor does it share antigens with prototypes of orthomyxoviruses, paramyxoviruses or arenaviruses. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Neither hemagglutination nor neuraminidase activities are detectable in virus preparations. No antigenic relationships were detected in serological assays using antisera against two orthomyxoviruses, a paramyxovirus, an atypical paramyxovirus, and an arenavirus (Beckwith, 1974(Beckwith, , 1975.…”
Section: Biological Propertiesmentioning
confidence: 82%
See 4 more Smart Citations
“…Neither hemagglutination nor neuraminidase activities are detectable in virus preparations. No antigenic relationships were detected in serological assays using antisera against two orthomyxoviruses, a paramyxovirus, an atypical paramyxovirus, and an arenavirus (Beckwith, 1974(Beckwith, , 1975.…”
Section: Biological Propertiesmentioning
confidence: 82%
“…Hoffman et al (1969) reported that the bluegill virus was 70-80 nm in diameter, was rather uniform in electron density, and resembled a myxovirus. Beckwith (1974Beckwith ( , 1975, however, reported that the virus was pleomorphic, varying from 80 to 250 nm in diameter, and contained electron-dense granules -20 nm in diameter. Beckwith suggested that the bluegill virus resembled an arenavirus or an atypical paramyxovirus.…”
Section: Morphologymentioning
confidence: 94%
See 3 more Smart Citations